2022
DOI: 10.1002/cac2.12291
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts in breast cancer: Challenges and opportunities

Abstract: CAFs exhibit significant heterogeneity in cancers, including breast cancer [5]. Due to the lack of perfect biomarkers for CAFs, CAFs are assessed by detecting a combination of different biomarkers. Different biomarker expression patterns have been identified in CAFs, and CAFs have been divided into diverse subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 366 publications
3
69
0
Order By: Relevance
“…The study confirmed that Twist1-Prrx1-TNC can form a positive feedback loop to induce the activation of CAFs (Yeo et al, 2018). In addition, CD44, a cell surface molecule expressed by MSCs, can also induce the activation of CAFs by up regulating Twist transcription (Spaeth et al, 2013;Hu et al, 2022). Myristoylated alanine-rich protein kinase C substrate (MARCKS), the forkhead box F1 gene (FoxF1), and the zinc finger transcription factor (snail 1) by activating AKT/ Twist1 signaling to upregulate αSMA and PDGFR, the release of paracrine factors such as FGF-2 and HGF is promoted, resulting in the activation of CAFs and tumor (Saito et al, 2010;Stanisavljevic et al, 2015;Yang et al, 2016a).…”
Section: Origins and Activators Of Cafssupporting
confidence: 55%
“…The study confirmed that Twist1-Prrx1-TNC can form a positive feedback loop to induce the activation of CAFs (Yeo et al, 2018). In addition, CD44, a cell surface molecule expressed by MSCs, can also induce the activation of CAFs by up regulating Twist transcription (Spaeth et al, 2013;Hu et al, 2022). Myristoylated alanine-rich protein kinase C substrate (MARCKS), the forkhead box F1 gene (FoxF1), and the zinc finger transcription factor (snail 1) by activating AKT/ Twist1 signaling to upregulate αSMA and PDGFR, the release of paracrine factors such as FGF-2 and HGF is promoted, resulting in the activation of CAFs and tumor (Saito et al, 2010;Stanisavljevic et al, 2015;Yang et al, 2016a).…”
Section: Origins and Activators Of Cafssupporting
confidence: 55%
“…For several cancer types including hepatocellular carcinoma, pancreatic cancer, breast cancer, lung cancer, melanoma, and colon cancer it has been demonstrated that tumor cells interaction with CAFs promotes EMT and the metastatic phenotype (Kubo et al, 2016;Domen et al, 2021;Shelton et al, 2021;Ahmad Zawawi and Musa, 2022;Ando et al, 2022;Hu et al, 2022). Direct and indirect mechanisms have been shown to influence tumor metastasis by CAFs: i) ECM remodeling by secretion of collagens, fibronectin, and proteoglycans (Scott et al, 2019); ii) paracrine communication through exosomes, growth factors and cytokines that promote stemness and metastasis, such as: transforming growth factor β -TGFβ, Chemokine (CC motif) ligand 2 (CCL2), Interleukin-6 (IL-6), Hepatocyte growth factor (HGF), Osteopontin (OPN) and Stromal cell-derived factor 1 (SDF-1) (Linares et al, 2020); iii) direct contact with cancer cells and facilitated invasion and select gene transcription (Yamaguchi and Sakai, 2015;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Co-culturing of breast tumor cells and fibroblasts increases cancer cell growth via metabolic reprogramming of fibroblasts producing Lactase and 3-Hydroxybutyrate, a hallmark of CAFs [ 68 ]. Studies have shown that CAFs differ from fibroblasts in adjacent normal breast tissue, as they have distinct mRNA and protein expression profiles and might impact the transcriptional profile of BC cells [ 69 , 70 ]. It is now thought that the altered phenotype of CAFs is mainly due to epigenetic modulation of the DNA [ 71 ].…”
Section: Notch Signaling Regulates Bc Progressionmentioning
confidence: 99%